Effects of Exercise on Appetite-Regulating Hormones, Perceived Hunger, and Energy Intake: A Narrative Overview - Marsa Gleason; Basil H. Aboul-Enein; Josh Bernstein; Joanna Kruk (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
Controlling appetite, perceived hunger, and energy intake are important factors in weight management. This narrative review examines the effect of different forms, intensities and duration of exercise on the appetite-regulating hormones leptin, acylated ghrelin, glucagon like peptide-1 (GLP-1) and peptide tyrosine tyrosine3-36 (PYY3-36), perceptions of hunger, and energy intake in overweight/obese, and normal weight populations. The studies reviewed compared exercise intensities- low, moderate, and high intensity, and modes of exercise- aerobic and resistance training. The studies selected in this narrative review included participants that ranged in age from 13-57 years old, male and female, previously sedentary and physically active, and normal weight and overweight/obese individuals- defined by body mass index standards (BMI). The primary benefits of exercise on appetite regulation are seen with moderate to high-intensity aerobic exercise; with the most notable relative energy deficit resulting from an exercise bout (at any intensity) that expends the most energy. Further research is warranted to determine if there exists a tendency to overcompensate for energy expended during exercise in certain populations.